Perinatal outcomes of congenital heart disease after emergent neonatal cardiac procedures. (18th October 2018) - Wolter, Aline; Holtmann, Helene; Kawecki, Andreea; Degenhardt, Jan; Enzensberger, Christian; Graupner, Oliver; Akintürk, Hakan; Yerebakan, Can; Khalil, Markus; Schranz, Dietmar; Axt-Fliedner, Roland
Abstract: Purpose: We compared outcome of neonates with prenatal and post-natal diagnosis of congenital heart disease presenting in our paediatric heart centre between March 2005 and May 2015 who underwent an emergent intervention within 48 h post-partum. Materials and methods: In 52/111 (46.8%) with emergent intervention, congenital heart disease was diagnosed prenatally, in 59/111 (53.2%) with no specialized foetal echocardiography, diagnosis was made post-natally. In 98/111 (88.2%), 30-day outcome was known. Results: Regarding the entire cohort, 30-day survival did not differ significantly in prenatal and post-natal diagnosis group (71.2 vs. 72.9%; p > .1). Infants with prenatal diagnosis were more likely to be born by caesarean section (59.6% vs. 33.9%, p = .01). Those with post-natal diagnosis had a higher need for intubation (32.7% vs. 52.5%; p < .05). Subgroup analysis of HLH/HLHC (hypoplastic left heart/hypoplastic left heart complex) patients revealed higher number of deaths within 30 days of life in the post-natal diagnosis group, although the difference did not reach statistical significance (5/7, 71.4% vs. 5/20, 25.0%; p = .075). Conclusion: For newborns who require emergent neonatal cardiac procedures, our results point towards a lower death rate after prenatal diagnosis of HLH/HLHC.